Perception sectorielle face À la nécessité d’une vision globale et partagée de l’estuaire de la Seine - Jean-Claude Dauvin (VertigO)
The estuary of the Seine is a continuum between its upstream part (the watershed and its input in the hydrological system) and the downstream part (the Seine Bay and the eastern part of the English Channel). However, according to, their sensitivities, scientists, administrators or policy makers consider various limits of this interface constituted of diversified natural heritage environments but strongly made man modified. The degradation of the Seine estuary began in the middle of 19th with the decreasing of the water quality, the contamination of the ecosystem and the reduction of the intertidal surfaces by the silting of industrial and harbour surfaces. Nevertheless, since the 1980’s, several indicators show the improvement of the estuary quality but other contaminants remains important, i.e. PCB, PAH, and endocrine biomarkers … In spite of all these natural and anthropogenic constraints, the Seine estuary shows remaining high specific and habitat diversities. After a phase of increasing of the knowledge on the structure and the functioning of the Seine ecosystem (Phases 1 - 3 of the Seine-Aval programme), the ambition of the programme is to restore the estuarine functionalities. But the nowadays harbour projects continue to maintain the existing ecological compartments of the Seine estuary and are still studied independently. It is necessary to support the promotion of a Global Management Plan of the Seine Estuary, and to surpass the sector-based vision to a global vision. Moreover, the ecologists can share this ecosystem-based management, i.e. a global holistic spatio-temporal approach.